Real-time Unmanned Surface Robot (USR) for river quality monitoring systemm - Mohd Aras, Mohd Shahrieel; Ponusamy, Pavitrah; Md Nawawi, Mohamad Riduwan; Zohedi, Fauzal Naim; Bahar, Mohd Bazli; Abdullah, Lokman; Khamis, Alias; Rizman, Zairi Ismael (Universitas Mercu Buana, 2026)
A real-time Unmanned Surface Robot (USR) for river water quality monitoring system is a technology that employs a small autonomous boat outfitted with sensors and other monitoring equipment to gather and transmit data on various water quality parameters like pH, temperature and total dissolved solids sensors in rivers and other bodies of water. The USR can traverse the river, gather information or data at specific points or designated locations, as well as continuously monitor a specific stretch of river at all times. The data or information was sent in real time to a central monitoring station, where it was analyzed and used to identify potential water quality problems. Initially, the USR was designed using SolidWorks software, and its structural performance was the main focus of the investigation and examination of the design. This USR was then created and manufactured. The entire USR system could help detect and mitigate pollution and other environmental problems, as well as offer useful information for managing water resources. Next, to determine the overall performance of the USR, five experiments and autopilot accuracy tests were performed. Finally, this study also verified and validated the accuracy of water quality monitoring sensors.